Effect of Time Management Training on Lifestyle of Nurses Working at General Surgery Wards of Hospitals in Sari Affiliated to Mazandaran University of Medical Sciences, 2016 - Khoshgoyan, Maryam; Zohari Anboohi, Sima; PourShirvani, Azita; Nasiri, Malihe (Advances in Nursing & Midwifery, 2018)
Abstract Background and objective: time management skills are necessary for success and promotion of clinical competency of nurses. Effective use of time is one of the unavoidable necessities for success in work and life and is considered as one of the methods to create balance between work and life aspects. Time management includes the use of skills to control and use time. This study aimed to determine the effect of time management training on lifestyle of nurses working in medical surgical wards of selected hospitals of Sari under the supervision of Medical University of Mazandaran in 2016. Material and methods: this intervention study was conducted on 70 nurses working in medical surgical ward of selected hospitals of Sari. Samples were selected by the available sampling method. Subjects were divided into control and experimental groups. Data were gathered by two questionnaires including demographic information and Walker’s Health Promoting Lifestyle Profile (1987) before and after time management skills training. The validity of instruments was examined and necessary modifications were done. The reliability of instruments was measured by Cronbach’s alpha (0.83). Time management skills were instructed for 3 hours in two sessions for the experimental group. After a month, all participants in two groups again completed the questionnaire. Data were analyzed using SPSS 22, descriptive and analytical statistics such as mean, standard deviation, absolute and relative frequency, independent t-test, and pairwise t-test. Findings: control group and experimental group were similar in terms of demographic variables and lifestyle in all aspects and no significant difference was observed. One month after intervention, no significant difference was observed between variables. Scores in all aspects and total score of lifestyle in both groups before and after intervention showed a significant difference. Conclusion: the findings of this study showed that time management training influences lifestyle at all aspects and total score. Therefore, some efforts should be applied to train time management skills and lead to improved lifestyle. Therefore, it is recommended to consider time management training in programs for nurses.